1999
DOI: 10.1175/1520-0477(1999)080<1077:tfiwac>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Fluctuations in Weather and Climate Extremes That Cause Economic and Human Health Impacts: A Review

Abstract: This paper reviews recent work on trends during this century in societal impacts (direct economic losses and fatalities) in the United States from extreme weather conditions and compares those with trends of associated atmospheric phenomena. Most measures of the economic impacts of weather and climate extremes over the past several decades reveal increasing losses. But trends in most related weather and climate extremes do not show comparable increases with time. This suggests that increasing losses are primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
265
0
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 415 publications
(280 citation statements)
references
References 33 publications
8
265
0
7
Order By: Relevance
“…Our method may also be used to predict the future behavior of extreme precipitation (Nadarajah and Choi 2003;Nadarajah 2005). Because the society has become more vulnerable to extreme precipitation due to population increase and economic growth (Kunkel et al 1999), the changing nature of return levels of extreme precipitation, should be taken into account for design practices and flood protection. The best fitting model was used to estimate the return levels for selected return periods (5, 10, 20, 50, 100, 200 and 500), for all of the four time series at each station.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our method may also be used to predict the future behavior of extreme precipitation (Nadarajah and Choi 2003;Nadarajah 2005). Because the society has become more vulnerable to extreme precipitation due to population increase and economic growth (Kunkel et al 1999), the changing nature of return levels of extreme precipitation, should be taken into account for design practices and flood protection. The best fitting model was used to estimate the return levels for selected return periods (5, 10, 20, 50, 100, 200 and 500), for all of the four time series at each station.…”
Section: Resultsmentioning
confidence: 99%
“…Variations in frequency, and intensity of extreme weather events, greatly affect the human societies and their environments (Kunkel et al 1999). During the past 50 years, there have been frequent extreme precipitation events causing severe floods and damaging the economy and environment in China.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, global climate change is expected to have a considerable impact on the global hydrological cycle. It has been seen that the economy, human health and the natural environment are becoming vulnerable to the extreme climate events [Easterling et al, 2000;Kunkel et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are very few studies about this topic, probably because of the lack of high-quality daily data. Some studies were performed for the USA (Karl et al, 1995;Karl and Knight, 1998;Trenberth, 1998;Kunkel et al, 1999), Japan (Iwashima and Yamamoto, 1993), eastern and northeastern Australia (Suppiah and Hennessy, 1998;Hennessy et al, 1999;Plummer et al, 1999), South Africa (Mason et al, 1999), the UK (Osborn et al, 2000) and Italy (Brunetti et al, 2000c(Brunetti et al, , 2001. Karl et al (1995) and Karl and Knight (1998) observed a significant positive trend in the frequency of extreme rainfalls (greater than 50 mm per day) over the last few decades in the USA.…”
Section: Introductionmentioning
confidence: 99%